1994
DOI: 10.1016/0014-5793(94)00991-0
|View full text |Cite
|
Sign up to set email alerts
|

The organisation of the multigene family which encodes the major cell surface protein, pMGA, of Mycoplasma gallisepticum

Abstract: The genome of the avian pathogen Mycoplasma galhsepticum contains a number of related genes for putative adhesion molecules @MGA). Cloning and sequence analysis of several pMGA genes suggested that all of them might be transcriptionally and translationally functional. Analysis of the gene sequence encoding the sole pMGA variant expressed in vitro in the S6 strain (pMGAl.1) revealed no unambiguous feature that could account for its unique expression. It is estimated that the pMGA gene family may contain up to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(123 citation statements)
references
References 10 publications
(8 reference statements)
2
121
0
Order By: Relevance
“…Variable proteins are often subjected to both size and phase variation, and many are members of multigene families. The proteins of a multigene family are often differentially expressed, and chromosomal rearrangements occur to allow transcription of one gene instead of another (Lysnyansky et al, 1999;Citti et al, 2000;Markham et al, 1994Markham et al, , 1999 FlitmanTene et al, 2000; Glew et al, 2000; Roske et al, 2001;Shen et al, 2000;Horino et al, 2003;Noormohammadi et al, 1998).…”
Section: -7247 G 2004 Sgm Printed In Great Britain 4009mentioning
confidence: 99%
See 1 more Smart Citation
“…Variable proteins are often subjected to both size and phase variation, and many are members of multigene families. The proteins of a multigene family are often differentially expressed, and chromosomal rearrangements occur to allow transcription of one gene instead of another (Lysnyansky et al, 1999;Citti et al, 2000;Markham et al, 1994Markham et al, , 1999 FlitmanTene et al, 2000; Glew et al, 2000; Roske et al, 2001;Shen et al, 2000;Horino et al, 2003;Noormohammadi et al, 1998).…”
Section: -7247 G 2004 Sgm Printed In Great Britain 4009mentioning
confidence: 99%
“…Variable proteins are often subjected to both size and phase variation, and many are members of multigene families. The proteins of a multigene family are often differentially expressed, and chromosomal rearrangements occur to allow transcription of one gene instead of another (Lysnyansky et al, 1999;Citti et al, 2000;Markham et al, 1994Markham et al, , 1999 FlitmanTene et al, 2000; Glew et al, 2000; Roske et al, 2001;Shen et al, 2000;Horino et al, 2003;Noormohammadi et al, 1998).Mmymy SC was originally thought not to exhibit intraclonal variability, but a variable surface protein Vmm (Persson et al, 2002) that undergoes reversible phase variation has recently been identified. The vmm gene has been demonstrated in all Mmymy SC strains as a single copy and is regulated at the transcriptional level by dinucleotide (AT) insertions or deletions in a repetitive region of the promoter spacer.…”
mentioning
confidence: 99%
“…The size of this message corresponded to the length of the vlhA gene from the transcriptional initiation site (Noormohammadi et al, 2000) to the predicted transcriptional termination site (stem loop). Thus, as in M. gallisepticum (Markham et al, 1994;Glew et al, 1995), the vlhA gene transcript in M. synoviae is monocistronic. In an earlier study (Noormohammadi et al, 1997) we described two clones of M. synoviae that differed in their capacity to adsorb red blood cells and to express the fulllength vlhA gene products, MSPB and MSPA.…”
Section: Discussionmentioning
confidence: 83%
“…Identification of T and B cell epitopes on different Mycoplasma strains become even more relevant since evasion mechanisms used by these bacteria to escape host immune response are based on antigen mimicry and antigenic variability (Markham et al, 1994;Wren, 2000 (Figure 1). The S 263 -D 277 peptides represent the most conserved B cell epitope which possesses 100% identity with peptides of the VhlA from the M. synoviae K1968, MS-H, ULB925 and ULB925KF strains and also with M. gallisepticum S6 and R strains (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Printed in Brazil www.sbg.org.br Escaping the host immune system is of critical importance to mycoplasma survival within its host. The major survival mechanisms that have been extensively studied are molecular mimicry and phenotype plasticity which ensure that mycoplasmas are not fully nor efficiently recognized by the host immune system (Markham et al, 1994;Wren, 2000). Molecular mimicry refers to antigenic epitopes that are shared by different mycoplasmas and host cells and they are considered as putative factors involved in the evasion of host defense mechanisms (Rottem, 2003).…”
Section: Introductionmentioning
confidence: 99%